Social data visualization with HTML5 and JavaScript : leverage the power of HTML5 and JavaScript to build compelling visualizations of social data from Twitter, Facebook, and more /: leverage the power of HTML5 and JavaScript to build compelling visualizations of social data from Twitter, Facebook, and more. (2013) - Unknown
No abstract available